PREPARASI DAN KARAKTERISASI KATALIS Ni-Mo/ZEOLIT ALAM SEBAGAI KATALIS PERENGKAHAN SAMPAH PLASTIK HDPE (Indonesian Journal of Chemical Science, 2012)
Preparation and characterization of the bimetallic catalyst Ni-Mo into natural zeolite active has been investigated. The preparations of catalysts were performed by insertion of sequence differences Ni-Mo metal into the natural zeolite and varying the rasio metal amount of 1%, 3% and 5% w/w.  The purpose of this study is to investigate the characteristics of the catalyst Ni-Mo/ZA and Mo-Ni/ZA, then applied in the process of catalytic cracking HDPE plastic waste. Activation of natural zeolites include treatment with an acid and salt (HCl 6M and NH4Cl 1N). Further Ni and Mo was impregnated into zeolite with the order : Mo in the first, then Ni to form Ni-Mo/ZA catalyst and Ni in the first then Mo to  Mo-Ni/ZA catalyst with a ratio Ni:Mo 1:2. Calcination with N2 at 500oC, oxidation with O2 and reduction with H2 at 400oC. The characterization of catalysts included determination of metal content using Atomic Absorption Spectroscopy (AAS), the acidity of catalyst by gravimetric method, and the porosity of catalyst by BET method. Polyethylene plastic waste treated by the pyrolysis method at a temperature of 550oC while flowing N2. Hydrocracking process was operated in a flow- fixed bed reactor at 360°C; ratio of catalyst/feed 0.5 under hydrogen stream (20 mL/minutes) for 2 hours for each catalyst.  A  product analyzed by gas chromatography (GC) and gas chromatography-mass spectroscopy (GC-MS). Analysis of the products showed the greatest catalytic activity is a catalyst Ni-Mo/ZA 5% w/w with a product conversion percentage of 6.6299%. GC-MS analysis  showed that the liquid hydrocracking products has a chemical composition consisting of  ethyl alcohol and 2-propanone. Research shows that the distribution of the bimetallic Ni-Mo metal, metal amount impregnation, and the acidity of the catalyst was the most influential in the process of catalytic cracking reaction of HDPE plastic waste.